Maximize utilization of date palm residues to produce environmentally friendly fuel briquettes - Al-Hashem, Hassan A.; Al-Hammad, Abdulrahman S.; Azam, Mostafa M. (Emirates Journal of Food and Agriculture, 2023)
This study aimed to maximize the utilization of date palm residues and convert them into an environmentally friendly form of fuel. The residues of the date palm variety Khalas (leaf fronds and whole fronds) were used to produce fuel briquettes at three moisture contents (8, 10, and 12%) and four storage times (0, 15, 30, and 45 days). The mechanical, fuel, and quality properties of these briquettes were investigated. The results showed that the leaf fronds had the best results in terms of mechanical properties and fuel quality properties of the briquettes. The best results for compressive stresses for the leaf fronds were 24.98 MPa at 10% moisture content and for the whole fronds were 4.27 MPa at 12%. The second storage period gave the best results for all briquettes at the different moisture contents. The results showed significant effects of moisture content and storage period on mechanical properties. The hydrolysis time and durability of the briquettes increased with increasing moisture content. The calorific value of leaf fronds and whole fronds briquettes ranged between (17.78 and 18.12 MJ/kg) and (16.54 and 17.78 MJ/kg), respectively. These good quality briquettes can be handled and used, especially in rural areas where other energy sources are not available. Keywords: Calorific value; Date palm residues; Durability; Fuel value index; Modulus of elasticity